Legal Translation Studies as Interdiscipline: Scope and Evolution - Prieto Ramos, Fernando (Meta, 2014)
This paper offers an overview of the development of Legal Translation Studies as a major interdiscipline within Translation Studies. It reviews key elements that shape its specificity and constitute the shared ground of its research community: object of study, place within academia, denomination, historical milestones and key approaches. This review elicits the different stages of evolution leading to the field’s current position and its particular interaction with Law. The focus is placed on commonalities as a means to identify distinctive reference points and avenues for further development. A comprehensive categorization of legal texts and the systematic scrutiny of contextual variables are highlighted as pivotal in defining the scope of the discipline and in proposing overarching conceptual and methodological models. Analyzing the applicability of these models and their impact on legal translation quality is considered a priority in order to reinforce interdisciplinary specificity in line with professional needs.